Chapter 16: Effective collaborative climate change governance in urban areas (Edward Elgar Publishing, 2021)
International research suggests that city governments need to adopt a collaborative approach to the management of climate change and its impacts: local government cannot deal with the challenges of, or harness the solutions to, climate change alone. Reflecting this recognition, multi-level and collaborative forms of governance have emerged as important for ensuring that climate adaptation and mitigation responses are selected, implemented and sustained. Here we consider some of the crucial elements of effective collaborative governance of climate change that have emerged from international literature and lessons. We do so by using illustrative empirical case studies of African cities in Malawi and Zimbabwe to examine barriers and opportunities to the implementation and maintenance of collaborative governance mechanisms that build local level climate resilience.